Analisis Segmen Pasar Produk Handphone Berbasis Android di Lingkungan Mahasiswa di Banjarmasin - Abul Hasan Asyari; Arief Noviarakhman Zagladi (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2020)
This study aims to determine and analyze the market segment of android-based mobile users on college students in Banjarmasin. Sample used are 140 college Student. The variables used as a basis for segmentation are product attribute variables including indicators of quality, price, performance, durability, reliability, brand image, features, design, model, specifications, capacity, warranty and aesthetics. The analytical tool used is the K-Mean Cluster Analysis. The results showed that Cluster 1 is respondents who are concerned with price, performance, durability, features, specifications and warranty attributes. This cluster is named